The “Us” versus “Them” Dichotomy: A Case Study of Donald Trump’s rhetoric - Hristova, Rossitsa (Yearbook of the Department of Foreign Languages and Cultures, 2024)
This case study explores the use of “Us” versus “Them” dichotomy as a strategy for framing and shaping public opinion in the rhetoric used by Donald Trump in articles published in The New Yorker Magazine. The fact-finding is held by a qualitative research method, particularly textual analysis. Taking into consideration the global rise of nationalism, respectively populist rhetoric, the research attempts to find a correlation between political representation and language. Related to the latter, it aims to analyse focal linguistic features such as inclusive and exclusive pronouns, metaphors, analogies and oppositions. Hence, language is used to create and enhance distinction between an in-group (us) and out-group (them). The findings of the analysis show that the language features function in a way to establish identity, solidarity and not least – opposition, in order to achieve the ultimate goal, that is to say, shaping opinion and attracting support by the in-group and respectively weakening and marginalising the out-group. This research endeavours to prove the strength of the dichotomy “Us versus Them” as a powerful tool for constructing social identities and relationships through language so as to form social dynamics, and shape the political discourse in order to evoke collective action.